Avaliação da adesão de Staphylococcus spp. em resina acrílica específica para prótese ocular e alteração de cor de botões de íris artificiais, variando a cor e as técnicas de obtenção, ambos após desinfecção química - Moreno, Amália [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Considering that ocular prostheses restore esthetics and patient’s self-esteem, the materials used for prosthesis fabrication should present appropriate properties regarding indication and reliability after the disinfection procedures. So, the aim of this study was to assess the effectiveness of different disinfectant solutions against two species of Staphylococcus spp. cultured on ocular prosthesis acrylic resin. In addition, the chromatic change of artificial iris buttons fabricated with different techniques was also evaluated before and after polymerization and disinfection. For the microbiology tests 396 acrylic specimens were fabricated (1.0 cm in diameter and 0.3 cm in thickness). Half of the samples were made for biofilm formation of S. epidermidis and half were made for biofilm formation of S. aureus, both on the sample surface. For each strain, 66 samples were underwent to biofilm formation on the liner surface for three different points: initial (24h), intermediate (48h) and mature (72h). Afterwards the specimens were randomly assigned (unit sample n = 6) to one of disinfectant treatments: distilled water for 10, 15, 30 min and 6 h (control-CTL); treated with neutral soap (NES) for 30 min; treated with Opti-Free (OPT) for 30 min and 6 h; treated with Efferdent (EFF) for 15 min; and treated with (0.5%, 2% and 4%) chlorhexidine gluconate (CHX) for 10 min. After the treatments, the specimens were vortexed to disrupt the biofilm, and residual cells were counted (cell/mL). For the color meansurations a total of 300 samples simulating ocular prosthesis were fabricated. Half of the samples were made with blue artificial irises, and half were made with brown artificial irises. For each color, 50 samples were fabricated according to one of the following techniques: PE - conventional technique, CA - prefabricated...

As próteses oculares são responsáveis pela recuperação da estética e auto-estima do usuário. Assim, os materiais utilizados na confecção de prótese ocular devem possuir propriedades específicas para sua indicação e durabilidade principalmente aos procedimentos de desinfecção pelo paciente. Desse modo, este estudo teve como objetivo verificar a efetividade de diferentes soluções desinfetantes na remoção de biofilme de duas espécies de Staphylococcus spp., desenvolvidas na superfície de resina acrílica específica para prótese ocular e avaliar a alteração de cor de botões de íris artificiais confeccionadas por diferentes técnicas antes e após a polimerização e quando influenciadas pela desinfecção química. Para o teste de microbiologia, 396 amostras em resina acrílica para prótese ocular N1 foram confeccionadas (1,0 cm em diâmetro e 0,3 cm em espessura), sendo metade dessas amostras para formação de biofilme de S. epidermidis e a outra metade para formação de biofilme de S. aureus, ambos na superfície da amostra. Para cada cepa bacterina, 66 amostras foram submetidas a formação de biofilme em sua superfície durante três diferentes tempos: inicial (24h), intermediário (48h) e maduro (72h). Em seguida as amostras foram distribuídas aleatoriamente (unidade amostral n=6) para um dos tratamentos desinfetantes: água destilada durante 10, 15, 30 min e 6 h (controle-CTL); sabão neutro (NES) durante 30 min; Opti-Free durante 30 min e 6 h; Efferdent (EFF) durante 15 min; e gluconato de clorexidina (0,5%; 2% e 4%) (CHX) durante 10 min. Após o tratamento desinfetante, as amostras acrílicas foram imediatamente agitadas para desprendimento do biofilme. A contagem de colônias foi verificada por análise do número de UFC/mL. Para a análise de alteração de cor 300 amostras simulando próteses oculares foram confeccionadas, sendo metade...
Keywords: Desinfecção; Olhos artificiais; Cor; Resinas acrilicas; Protese maxilo-facial; Biofilme; Disinfection